Business Feasibility Review and Environmental Aspects: Case Study of PT. Sekar Laut Tbk, Sidoarjo Regency in an Amdal Perspective - Nuzhuliya Mega Avifa; Abdur Rohman (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Promoting sustainable development and controlling the use of natural resources is the goal of environmental management. To achieve this goal, from the beginning of planning activities, changes in environmental conditions due to development activities must be estimated, both beneficial (positive) and detrimental (negative) consequences. Thus, from an early age, management steps must be prepared. One way to assess the likelihood of environmental changes is to conduct an EIA study. The research method used in this study is qualitative through document research, especially legal research that considers law as a constructive norm system. The results of this study show that PT Sekar Laut carries out its manufacturing activities according to the EIA aspect.